FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PERIKSA PAYUDARA SENDIRI (SADARI) PADA WANITA USIA SUBUR DI PUSKESMAS DEPOK I SLEMAN YOGYAKARTA - Pramukti Dian Setianingrum; Melinda Eka Rachmasari (STIKes Surya Global Yogyakarta, 2018)
Background : Breast cancer is a malignancy of the cells found in the breast tissue, can be derived from components of the glans (or lobulusnya tract epithelium) and components in addition to the glands such as fat tissue, blood vessels and persyarafan breast tissue breast tissue. Currently breast cancer is the second cause of cancer death in women, after cervical cancer and is the cancer most commonly encountered in women. The percentage of cancer patients in Yogyakarta highest in Indonesia reached 4.1%. Objective : This research is conducted to determine the influence of knowledge, attitudes, facilities-health, behavior and attitude of health workers to conduct breast self-examination and to determine the most significant effect on the behavior of breast self-examination at the health center Depok I Sleman, Yogyakarta. The independent variables in this study is the knowledge, attitudes, facilities-behavioral health facilities and the attitude of health workers, dependent variable in this study is the behavior of breast self-examination. The populations in this study as many as 339 people with a sample of 80 people. Sampling technique used by the method of accidental sampling and testing techniques of data used in this study include validity, and reliability with Cronbach alpha. Univariate analysis, bivariate analysis, using Kendall-tau test. Result : There is no influence between knowledge and behavior of breast self-examination at the health center Depok I Sleman Yogyakarta with the results of the correlation is 0.061 0.05. And there are two influence between attitudes and behaviors of health workers with the behavior of breast self-examination with the results of the correlation is 0.029 0.005 and 0.000 0.005. Conclusion : The conclusion of this research shows that there is no positive and significant influence between knowledge and behavior of breast self-examination, there is influence between attitudes and behavior of breast self-examination and the mindsets of officers with breast selfexamination.